Plínio Salgado. - Bertonha, João Fábio, author.
1 online resource.
Keywords: "Plínio Salgado covers the life trajectory of the far-right Brazilian political leader between 1895 and 1975. The book initially follows his life from his birth, including political and cultural training and political activities between 1895 and 1930. The focus then shifts to his period as leader of the Brazilian fascist movement between 1932 and 1938, with attention to his performance as a leader, his role within the movement, and in the rise and fall of the Integralist Action. His period of exile in Portugal between 1939 and 1947 is also emphasized, with a special focus on his contacts with the Portuguese radical right and German and Italian agents. The final part addresses his return to Brazil, his efforts to reposition himself politically and his performance as a parliamentarian and supporter of the military coup of 1964. This book will be of interest to researchers of Latin American history, Brazilian history and politics, the transnational far right, and comparative fascism studies"--